2007
DOI: 10.3200/jrlp.141.5.525-538
|View full text |Cite
|
Sign up to set email alerts
|

Mindless Decision Making and Environmental Issues: Gestalt/Feature-Intensive Processing and Contextual Reasoning in Environmental Decisions

Abstract: In the absence of relevant information in working memory during decision consideration, respondents tend to rely on a style of cognitive processing that may result in premature or inaccurate decision making (M. J. Sharps, 2003). M. J. Sharps and S. S. Martin (2002) demonstrated this effect in executive decision making. In the present study, the authors extended these methods to decisions about environmental issues. Respondents rated decisions about issues such as overpopulation, energy policy, and food product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Such inattentional blindness (Simons & Chabris, 1999) also occurs when people receive automated decision support in process control environments: They fail to cross-check information, especially when the degree of automation is high (Manzey et al, 2012). When evaluating situations, people sometimes do not take into account information about contextual constraints and possible negative consequences (Sharps et al, 2007;Sharps & Martin, 2002). This even is the case for very simple, well-known information.…”
Section: Selecting and Ignoring Particular Types Of Informationmentioning
confidence: 99%
“…Such inattentional blindness (Simons & Chabris, 1999) also occurs when people receive automated decision support in process control environments: They fail to cross-check information, especially when the degree of automation is high (Manzey et al, 2012). When evaluating situations, people sometimes do not take into account information about contextual constraints and possible negative consequences (Sharps et al, 2007;Sharps & Martin, 2002). This even is the case for very simple, well-known information.…”
Section: Selecting and Ignoring Particular Types Of Informationmentioning
confidence: 99%
“…In fact, if the relevant information is kept only in long-term memory, it can be of reduced use for an effective understanding in a given situation. For decisions to be informed by memory, some relevant aspects should be adjoining the situation of decision-making, immediately available in working memory 33 . However, this type of memory is limited to a few items, regardless of the complexity of the task 15 , requiring a careful selection of the most relevant information 16 .…”
Section: The Mediating Role Of Memory In Attention and Anticipationmentioning
confidence: 99%
“…Firstly, they treat decision-making as a purely academic exercise, a logic game, which is performed almost in a 'social vacuum'. This fails to take account of the manner in which individuals make operational decisions as parts of complex practical tasks and, critically, within complex cultural, social and institutional contexts (see Key & Schwartz, 2007;Sharps, Hess, & Ranes, 2007;Sharps & Martin, 2002;Thompson, 2003). Secondly, a range of subsequent studies have demonstrated that decision makers in everyday circumstances are often motivated to make a 2 These domains include economics, mathematics, psychology, and many others.…”
Section: Sport and Decision-makingmentioning
confidence: 99%